Health Information Technology Challenges to Support Patient-Centered Care Coordination - Séroussi, B.; Jaulent, M.-C.; Lehmann, C. U. (Yearbook of Medical Informatics, 2015)
Objectives: To provide an editorial introduction to the 2015 IMIA Yearbook of Medical Informatics.Methods: We provide a brief overview of the 2015 special topic “Patient-Centered Care Coordination”, discuss the addition of two new sections to the Yearbook, Natural Language Processing and Public Health & Epidemiology Informatics, and present our editorial plans for the upcoming celebration of the 25th anniversary of the Yearbook.Results: Care delivery currently occurs through the processing of complex clinical pathways designed for increasingly multi-morbid patients by various practitioners in different settings. To avoid the consequences of the fragmentation of services, care should be organized to coordinate all providers, giving them the opportunity to share the same holistic view of the patient’s condition, and to be informed of the planned clinical pathway that establishes the roles and interventions of each one. The adoption and use of electronic health records (EHRs) is a solution to address health information sharing and care coordination challenges. However, while EHRs are necessary, they are not sufficient to achieve care coordination, creating information availability does not mean the information will be accessed. This edition of the Yearbook acknowledges the fact that health information technology (HIT), and EHRs in particular, are not yet fully addressing the challenges in care coordination. Emerging trends, tools, and applications of HIT to support care coordination are presented through the keynote paper, survey papers, and working group contributions.Conclusions: In 2015, the IMIA Yearbook has been extended to emphasize two fields of biomedical informatics through new sections. Next year, the 25th anniversary of the Yearbook will be celebrated in grand style! A special issue with a touch of reflection, a bit of rediscovery, and some “science-fiction” will be published in addition to the usual edition.
Keywords: Editorial; 2015 IMIA Yearbook of Medical Informatics; Patient-Centered Care Coordination; survey of biomedical informatics; IMIA and its societies